2021
DOI: 10.1021/acsinfecdis.0c00661
|View full text |Cite
|
Sign up to set email alerts
|

Synergy of the Polymyxin-Chloramphenicol Combination against New Delhi Metallo-β-Lactamase-Producing Klebsiella pneumoniae Is Predominately Driven by Chloramphenicol

Abstract: Carbapenem-resistant Klebsiella pneumoniae has been classified as an Urgent Threat by the Centers for Disease Control and Prevention (CDC). The combination of two “old” antibiotics, polymyxin and chloramphenicol, displays synergistic killing against New Delhi metallo-β-lactamase (NDM)-producing K. pneumoniae. However, the mechanism(s) underpinning their synergistic killing are not well studied. We employed an in vitro pharmacokinetic/pharmacodynamic model to mimic the pharmacokinetics of the antibiotics in pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 54 publications
1
21
0
Order By: Relevance
“…The metabolites were selected based on the previous transcriptomic and metabolomic findings ( Maifiah et al, 2017 ; Han et al, 2018 ; Hussein et al, 2018 ; Abdul Rahim et al, 2021 ), which indicated that the intracellular levels of metabolites R5P, UACGAM, and GLYC3P were significantly perturbed by polymyxin. Furthermore, metabolites PHPYR, OROT, 3PG, and 3PHP have also been identified as significant metabolites perturbed by the combination ( Abdul Rahim et al, 2021 ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The metabolites were selected based on the previous transcriptomic and metabolomic findings ( Maifiah et al, 2017 ; Han et al, 2018 ; Hussein et al, 2018 ; Abdul Rahim et al, 2021 ), which indicated that the intracellular levels of metabolites R5P, UACGAM, and GLYC3P were significantly perturbed by polymyxin. Furthermore, metabolites PHPYR, OROT, 3PG, and 3PHP have also been identified as significant metabolites perturbed by the combination ( Abdul Rahim et al, 2021 ).…”
Section: Resultsmentioning
confidence: 99%
“…The metabolites were selected based on the previous transcriptomic and metabolomic findings ( Maifiah et al, 2017 ; Han et al, 2018 ; Hussein et al, 2018 ; Abdul Rahim et al, 2021 ), which indicated that the intracellular levels of metabolites R5P, UACGAM, and GLYC3P were significantly perturbed by polymyxin. Furthermore, metabolites PHPYR, OROT, 3PG, and 3PHP have also been identified as significant metabolites perturbed by the combination ( Abdul Rahim et al, 2021 ). Although many significant metabolites were identified from the studies, the selected metabolites were those that demonstrated perturbations to both gene expression and metabolism of the same pathway [e.g., gnd and R5P in the pentose phosphate pathway (PPP); pgk and 3PG in gluconeogenesis] by the combination ( Abdul Rahim et al, 2020 ; 2021 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“… Zhu et al (2018) integrated multi-omics data with a genome-scale metabolic model (GSMM) to analyze the responses of P. aeruginosa to polymyxins. Abdul Rahim et al (2021) employed a systems-based model to analyze the synergistic activity of polymyxin B and chloramphenicol. Wozniak et al (2020) adopted a combination of metabolomics and proteomics analysis of S. aureus bacteraemia together with the computational tool as biomarkers to predict mortality risk and recommend personalized therapy.…”
Section: Multi-omics and Metabolic Modellingmentioning
confidence: 99%